Peningkatan Hasil Belajar Materi Transformasi Pada Siswa Kelas IX Menggunakan Problem Based Learning Berbantuan Media Animasi - Nadek, Olfiana Marciana; Nenohai, Juliana M. H. (Fraktal : Jurnal Matematika dan Pendidikan Matematika, 2024)
This research was motivated by the mathematics learning results of class IXA UPTD students at SMP N 1 Landu Leko, Rote, especially in transformation material which was still low. The aim of this research is to improve the mathematics learning outcomes of class IXA UPTD SMP N 1 Landu Leko, Rote on transformation material especially reflection and translation. The type of research used is classroom action research (PTK) which refers to the Kemmis & Mc Taggart which consists of 4 stages, namely: 1) planning; 2) implementation; 3) observation; and 4) reflection. The data collection techniques used are observation and tests, while the data analysis is descriptive qualitative and quantitative. The results of this research show that the percentage of implementation of teacher teaching activities in cycle I was 97.5%, increasing to 100% in cycle II, the percentage of implementation of student activities in cycle I was 92.85%, increasing to 100% in cycle II, and the percentage of completion of results Classical student learning in cycle I was 60.86% and increased to 82.60% in cycle II. Thus, it can be concluded that the application of the problem based learning model assisted by animation media can improve the learning outcomes of class IXA UPTD students at SMP N 1 Landu Leko, Rote on transformation material (reflection and translation).